PPAR Ligands Function as Suppressors That Target Biological Actions of HMGB1 - Shibo Ying (PPAR Research, 2016)
High mobility group box 1 (HMGB1), which has become one of the most intriguing molecules in inflammatory disorders and cancers and with which ligand-activated peroxisome proliferator-activated receptors (PPARs) are highly associated, is considered as a therapeutic target. Of particular interest is the fact that certain PPAR ligands have demonstrated their potent anti-inflammatory activities and potential anticancer effects. In this review article we summarize recent experimental evidence that PPAR ligands function as suppressors that target biological actions of HMGB1, including intracellular expression, receptor signaling cascades, and extracellular secretion of HMGB1 in cell lines and/or animal models. We also propose the possible mechanisms underlying PPAR involvement in inflammatory disorders and discuss the future therapeutic value of PPAR ligands targeting HMGB1 molecule for cancer prevention and treatment.